Investment Environment in Ukraine - Misan, Yaroslav; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis is aimed to describe the investment environment in Ukriane and provide an understanding of the economic and political state of the country, highlighting ongoing challenges. Basic macroeconomic overview of the country, examination of administrative and legal framework, government incentives and existing FDI flows and sectoral composition of the economy. PESTEL together with Risks and Opportunities analysis provides an understanding of the country’s economic state and highlights important point for decision making when considering Ukraine as a potential investment destination.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses